Spousal violence in sub-Saharan Africa: does household poverty-wealth matter? - Bamiwuye, Samson Olusina (BioMed Central, 2014)
INTRODUCTION: Despite the threat of violence to the health and rights of women yet, for many years, there has been a dearth of nationally comparable data on domestic violence in sub-Saharan Africa. This paper examines whether women from poor households are more likely to experience violence from husband/partner than other women who are from middle or rich households. METHOD: Data for the study are derived from most recent DHS surveys of ever-married women age 15-49 in Cameroun(3,691), Kenya(4,336), Mozambique(5610), Nigeria (16,763), Zambia(3,010) and Zimbabwe(5,016) who participated in the questions on Domestic Violence Module. Bivariate analysis and Binary Logistic Regression Analysis are used to explore the linkage between household poverty-wealth and spousal violence while simultaneously controlling for confounding variables. RESULTS: The overall prevalence of any form of violence (physical, sexual or emotional) ranges from 30.5% in Nigeria to 43.4% in Zimbabwe; 45.3% in Kenya; 45.5% in Mozambique; 53.9% in Zambia and 57.6% in Cameroun. Both bivariate and multivariate analyses show that in two of the six countries –Zambia and Mozambique, experience of violence is significantly higher among women from non-poor (rich) households than those from other households (poor and middle). For Zimbabwe and Kenya, women from poor households are more likely to have ever experienced spousal violence than those from non-poor households. In the remaining two countries- Nigeria and Cameroun, women from the middle class are more likely to have ever suffered abuse from husband/partner than those from the poor and rich households. CONCLUSION: Our results thus show that similar measurements of household poverty-wealth have produced varying relationships with respect to experience of spousal violence in six sub-Saharan African countries. In other words, experience of violence cuts across all household poverty-wealth statuses and therefore may not provide enough explanations on whether household-poverty necessarily serves to facilitate the ending of violence. These results suggest that eliminating violence against women in sub-Sahara Africa requires a comprehensive approach rather than addressing household poverty-wealth alone.